2021
DOI: 10.1097/scs.0000000000007830
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection After Autologous Cranioplasty for Decompressive Craniectomy in Traumatic Brain Injury: A Retrospective Review of Two Level 1 Trauma Centers

Abstract: Object: Surgical site infection (SSI) after cranioplasty can result in unnecessary morbidity. This analysis was designed to determine the risk factors of SSI after cranioplasty in patients who received a decompressive craniectomy with the autologous bone for traumatic brain injury (TBI). Methods: A retrospective review was performed at two level 1 academic trauma centers for adult patients who underwent autologous cranioplasty after prior decompressive craniectomy for TBI. Demographic and procedural variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Diabetes has been associated with various postoperative morbidity, including postoperative infection after cranioplasty [3,4,6]. In this study, we also found a strong correlation between diabetes and infection.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Diabetes has been associated with various postoperative morbidity, including postoperative infection after cranioplasty [3,4,6]. In this study, we also found a strong correlation between diabetes and infection.…”
Section: Discussionsupporting
confidence: 78%
“…However, cranioplasties can have serious complications including infection, seizures, bone resorption, and delayed hydrocephalus [3] with an overall complication rate reported as high as 40% [4]. Among these complications, postoperative infection is one of the most important complications because it can lead to serious conditions including empyema and meningitis, that require a long period of intravenous antibiotics treatment and possibly multiple surgeries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Maye et al 40 267 4.5% NS: Intraoperative monitoring and 5-ALA f Only for neuro-oncology surgery. Caruso et al 41 71 4.2% NS: Postoperative drain placement; Administration of intrawound vancomycin powder; Prophylactic preoperative IV vancomycin is a protective factor; For autologous cranioplasty after decompressive craniectomy in TBI g . Alkhaibary et al 42 103 15.7% Blood glucose levels Skull defect size For Autologous Cranioplasty Valentini et al 43 6359 1.7% Younger patients (≤14 years) The number of surgeries Surgeries lasting longer than 3 hours Two or more surgeries with prosthetic implants ABP prolongation showed limited efficacy for wound complication.…”
Section: Risk Factors Of Carbapenem-resistant Enterobacteri...mentioning
confidence: 99%
“…The duration and complexity of the surgery also contribute to this heightened risk. Moreover, the variability in the type of pathogens responsible for SSIs, influenced by factors like the hospital environment, antibiotic resistance patterns, and individual patient microbiota, adds another layer of complexity to managing these infections 19 …”
Section: Introductionmentioning
confidence: 99%